Treatment of osteomyelitis in New Zealand white rabbit using impregnated biomaterials with gentamicin: in vivo study outcome of bacterial study and micro-computed topography evaluation - Zulkifly, Ahmad Hafiz; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli; Aziz, Aziah (Malaysian Orthopaedic Association (MOA), 2017)
INTRODUCTION: Treatment of osteomyelitis is still a major challenge in orthopaedic field. New Zealand White rabbit is acceptable experimental model described to develop effective local delivery of antibiotics osteomyelitis treatment as it can mimics the disease process in human. The objective of the study is to evaluate the outcome treatment of osteomyelitis in rabbit femur with impregnated Hydroxyappatite Gentamicin. Evaluation at stipulated durations using microCT Skyscan 1176 system. MATERIALS & METHODS: Osteomyelitis is created by inoculation of Staphylococcus aureus ATCC 25923 into rabbit’s distal femur. The rabbit were divided with 3, 6, 12, 26 week assessments. The response of the biomaterials (hydroxyapatite) impregnated with gentamicin against the infection were evaluated through microcomputed topography using Skyscan 1176 system.The bone analysis data were obtained by the software provided by Skyscan 1176 system. The distal femoral shaft were scanned using A1 1mm filter with 18 µm pixel resolutions. Bacterial study of culture and sensitivity, coagulase test, catalase test and gram stain were done to determine the treatment is effective. RESULTS: The data of bone analysis were for tissue volume (TV), bone surface (BS), bone volume (BV), and trabecular thickness (Tb.Th) in all groups were illustrated at Table 1. The bone healing noted in the treated group. The results showed no bacterial were grow in the agar and all test were negative at 26 weeks interval. Table 1 showing the bone analysis through Skyscan1176 system.